What are we eating? Consumer information requirement within a workplace canteen. (October 2016) - Price, Sarah; Viglia, Giampaolo; Hartwell, Heather; Hemingway, Ann; Chapleo, Chris; Appleton, Katherine; Saulais, Laure; Mavridis, Ioannis; Perez-Cueto, Federico J.A.
Highlights: Exploring information needs in workplace canteens. Analysis of information needs of 452 consumers in 4 EU countries. Value for Money, Nutrition and Naturalness are key elements of information. Abstract: The workplace is a captive environment where the overall contribution of the meal served could be an important element of the overall diet. Despite growing demand little information is available to aid healthy dish selection. This study identifies information valued by consumers in the UK, Greece, Denmark and France using best-worst scaling. Value for Money, Nutrition and Naturalness are key elements of information that consumers require to be able to make a conscious decision about dish selection in all four countries. Latent class analysis shows that consumers align to one of five cluster groups, i.e., Value Driven, Conventionalists, Socially Responsible, Health Conscious and Locavores. Understanding key information needs can allow food operators to align their service with consumer preferences across different market segments.